Zimbabwe : Second Review Under the Staff-Monitor Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Zimbabwe's Second Review of the Staff-Monitored Program. The program is on track. Four of the five quantitative targets for end-June 2015, and all the structural benchmarks for the second review were met. Although a recently contracted USD 200 million nonconcessional loan breached the quantitative target on nonconcessional borrowing, it avoided the accumulation of additional external arrears. The IMF staff welcomes the authorities' intentions to continue seeking financing through grants and loans that are as concessional as possible, and to limit contracting non-concessional loans to within the ceiling set under the program, and to prioritize investment that would eventually raise Zimbabwe's capacity to repay.